Credit Markets in an Emerging Economy: Evidence from Pakistan - Hussain, Inayat (Curtin University, 2017)
This thesis examines default resolution, fresh credit and lending relationships. The results suggest that collateral expedites both default resolution and access to fresh credit while higher interest rates increase duration of default. The impact of lender-borrower relationship on terms of credit varies by types of financial institution and firm. A longer relationship of a firm with the CEO of its bank results in lower risk premia.